What’s going on at the bus stop? The impact of Auckland’s real time passenger information system on patrons timespace perceptions - Phillipa Mitchell (Netcom)
Transport innovations have predominantly been recognised for their power to alter geographic space through time space compression. The emergence of Intelligent Transport Systems provides an interesting new lens through which to investigate individuals’ perceptions and constitution of time and space. This paper focuses on one of these systems, the Real Time Passenger Information Signal Pre-emption System (RTPISP System) currently being installed in Auckland, New Zealand. It explores how individuals’ travel experiences are being shaped by interface the RTPISP System provides between the ubiquitous computing background and individuals’ everyday lives. This paper proposes that such technologies are causing more than just the compression of space by time. By embedding the mundane activity of catching the bus in the coded spaces of the RTPISP System new conditions of possibility are emerging allowing these bus patrons to constitute alternative timespaces while waiting for the bus, timespaces which they previously were unable or unwilling to access.